The Art of Spirals - Pan, Hongjun (European Journal of Applied Sciences, 2022)
Interesting graphic patterns can be created by mathematically manipulating the spirals calculated by the galactic spiral equations. Such mathematical manipulation is achieved by multiplying the spiral data with a special mathematical function named as art-pattern function. This method can be extended to parametric curve equations other than spiral equations and to 3-dimension graphics. The graphic creativity is unlimited through this method. This method will have wide applications in many aspects of our daily life.